Parhyangan Universitas Pendidikan Ganesha, Buleleng, Bali (Sejarah, Struktur, Fungsi dan Potensinya Sebagai Sumber Belajar Sejarah di SMA) - Luh Ayu Martasari; Mudana, I Wayan; Purnawati, Desak Made Oka (Widya Winayata : Jurnal Pendidikan Sejarah, 2023)
This study aims to find out: (1) the history of the founding of the Ganesha University of Education Parhyangan in Buleleng, Bali, (2) the structure and function of the Ganesha University of Education Parhyangan, Buleleng, Bali and (3) the potential of the Ganesha University of Education Parhyangan as a source of history learning in high school. The research method used is the historical research method which consists of: Heuristics, source criticism or verification, interpretation, and historiography. The results showed that: Parhyangan Ganesha University of Education (Undiksha) at the Central Campus was built in 2003 and was inaugurated on June 2 2004 which was formerly still called IKIP Singaraja. The Parhyangan structure uses the Tri Mandala concept, in the Main Mandala area there are shrines for Ratu Taksu, Padmasana, Pelinggih Ganesha, Panglurah Agung, Linggih Bhatara Tirta and Bale Piasan. In the Madya Mandala area there is the Kiwe Tengen Temple, Bale Gong, Bale Pewaregan and the Inauguration Marker and in the Nista Mandala area there are Wantilan, Sulang Aing (Lebuh) and Toilets. Parhyangan also has four functions, namely the Religious Function as a place of worship, the Social Function as a place for Hindus to unite, the Cultural Function as a place for performing arts and the development of self-skills in both singing, dance and percussion arts, and the Educational Function as a place for non-formal learning in religious field. In addition, the potential of the Parhyangan of the Ganesha University of Education (Undiksha) on the Central Campus as a learning resource can be developed on spiritual aspects, knowledge aspects, social aspects and cultural aspects. Key words: Parhyangan, History, Structure, Function, Learning Resources